PEMANFAATAN LIMBAH ABUBATU SEBAGAIBAHAN PENGISI DALAM PRODUKSI SELF-COMPACTING CONCRETE - Siamet Widodo, Agus Santosa, Pusoko Prapto (Universitas Negeri Yogyakarta, 2006)
Abstractlimestone powder has been the traditional material used incontrolling the segregation potential and deformability of fresh selfcompacting concrete (SCC). This paper deals with the utilization ofalternative materials, such as quarry dust, for SCC applications. Thisexperimental tests aimed to observe the effects of stone dust role inSCC, that utilized by addition and partial replacement ranging from 0%.12,5%, 25% and 37,5% based on the weight of portland cernentmaterial. The tests were done on compressive strength and splittingtensile strength using three standard cylinder specimens for each data.Test results indicate that stone dust could improve the compressivestrength of see by addition method with the optimum dosage in 25°/ addition by weight of cement, but all test results indicate that stone dustwill decrease the splitting tensile strength of see both in addition andpartial replacement method.Keywords: self compacting concrete, filler, stone dust.compressive strength, splitting tensile strength.